DFT investigation of the potential of porous cages for the catalysis of ammonia borane dehydrogenation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2011)
Full DFT based quantum mechanical studies reveal that zero dimensional porous structures, especially the newly proposed phosphorus incorporated organic cages, can be excellent catalysts for the dehydrogenation of ammonia borane.